Application of Artificial Intelligence in Education: The Role of Technology as an Educational Tool - Triyo Supriyatno, Sutiah, Samsul Susilawati (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Because of its potential to completely transform conventional teaching methods, artificial intelligence (AI) has attracted a lot of attention from a variety of industries, including education. This essay addresses AI's potential as a teaching tool and examines its use in education. The main emphasis is on how AI technology may improve overall educational outcomes, personalise education, and enhance learning experiences. The paper starts off by giving a general introduction to artificial intelligence (AI) and its main ideas, such as deep learning, machine learning, and natural language processing. After that, it explores particular uses of AI in education, like chatbots that can tutor students and platforms that adapt to their needs. These technologies make use of AI algorithms to evaluate student data, offer individualised feedback, and design personalised learning pathways based on each learner's requirements and preferred method of learning. The study also looks at the advantages and difficulties of incorporating AI into educational environments. Benefits include increased access to a wealth of instructional resources, better learning efficiency, and more student involvement. To guarantee ethical and fair AI use in education, issues including algorithmic bias, data privacy concerns, and the requirement for teacher training in AI utilisation must also be addressed. The article also explores possible developments and future trends in AI-driven education, including AI-powered educational assistants, personalised learning ecosystems, and virtual reality simulations. These developments have the power to completely change education by improving accessibility, effectiveness, and engagement for students of all ages and backgrounds..